The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.langmuir.8b00652
|View full text |Cite
|
Sign up to set email alerts
|

Unified Scaling of the Structure and Loading of Nanoparticles Formed by Diffusion-Limited Coalescence

Abstract: The present study establishes the scaling laws describing the structure of spherical nanoparticles formed by diffusion-limited coalescence. We produced drug-loaded nanoparticles from a poly(ethylene glycol)-poly(d,l-lactic acid) diblock polymer (PEG- b-PLA) by the nanoprecipitation method using different types of micromixing chambers to explore multiple mixing regimes and characteristic times. We first show that the drug loading of the nanoparticles is not controlled by the mixing time but solely by the drug-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…However, when a microfluidic mixing method such as the staggered Herringbone mixing nanoprecipitation (SHMN) is compared to classical batch nanoprecipitation (BN), it is found that the process with the fastest mixing time (SHMN) produces smaller NPs with less batch-to-batch variability than BN 161 . On the other hand, size polydispersity index is greater for SHMN than BN, suggesting that size control remains a complex issue 161 . Polymer-stabilized colloids can be produced by surface modification by polymer grafting.…”
Section: Control Of Materials Assembly: Mixingmentioning
confidence: 99%
“…However, when a microfluidic mixing method such as the staggered Herringbone mixing nanoprecipitation (SHMN) is compared to classical batch nanoprecipitation (BN), it is found that the process with the fastest mixing time (SHMN) produces smaller NPs with less batch-to-batch variability than BN 161 . On the other hand, size polydispersity index is greater for SHMN than BN, suggesting that size control remains a complex issue 161 . Polymer-stabilized colloids can be produced by surface modification by polymer grafting.…”
Section: Control Of Materials Assembly: Mixingmentioning
confidence: 99%
“…Precise regulation of the flow rates provides a handle to control NP properties, such as size, by tuning the mixing time (Johnson and Prud'homme, 2003b;Saad and Prud'homme, 2016). Microfluidic devices based on hydrodynamic flow focusing have been used for formulation screening (µg min −1 ), while on-scale production (mg min −1 to g min −1 ) was achieved with impinging jet mixers and coaxial jet mixers (CJMs) (Karnik et al, 2008;Lim et al, 2014;Hickey et al, 2015;Liu et al, 2015;Rode García et al, 2018). In our recent work, we developed a CJM from off-the-shelf components for flow-based production of NPs that enabled tunable NP size in both formulation screening mode (∼µg min −1 ) and scalable production mode (∼mg min −1 ) (Bovone et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An upper limit of the residence time was estimated using the total uidic volume and ow rate. 39 The residence time was longer than the mixing time at all ow rates, indicating that complete mixing had occurred in the micromixer. The maximum shear rate was taken as the wall shear rate, with the assumptions that chaotic advection did not signicantly affect the wall shear rate and that it created a signicantly lower shear within the channel.…”
Section: Semimentioning
confidence: 91%
“… 38 An upper limit of the residence time was estimated using the linear velocity and the needle length. 39 The maximum shear rate was taken as the wall shear rate and, for simplicity, the shear rate calculations used the geometry of a straight cylinder. Calculations for the 3, 10 and 50 mL syringes used in the study were performed similarly, using the internal diameters stated by the manufacturer (Table S1 † ).…”
Section: Methodsmentioning
confidence: 99%